THE STUDY OF NATURALISM ON A THOUSAND SPLENDID SUN NOVEL - Mufidah, Nida (LET: Linguistics, Literature and English Teaching Journal, 2013)
Language teaching of literature is the way to encourage the students ability to give responses to what they read.  This way can in one hand promote literacy and critical thinking of the students and facilitate students to build a learner center environment in learning.  In this article the writer tries to raise and discuss a literature stream of a novel A Thousand Splendid Suns by Khaled Hosseini,it is still taking background of war going on in Afganistan. This novel has discussed the naturalism of literature which draws peoples lives that portrayed in the very low life, tragic, and pathetic. It tells the story of two women who are suffering due to war and forced marriage. It also deals with an infinite love, incredible affection, sacrifice and struggle of different ages of two women, but became one family because of a polygamous marriage. This novel not only tells the life-wrenching character with family conflict, but readers are also invited to imagine and to feel pain as a result of an endless war in Afghanistan. Literature may also have a wider educational function in the classroom in that, it can help to stimulate the imagination of students to develop their critical abilities and to increase their emotional awareness